65.9k views
1 vote
8 • 4 • k + 9 • 5 = (36 - 4)k - (2 • 5)

1 Answer

7 votes

Simplifying

8 * 4k + 9 * 5 = (36 + -4) * k + -1(2 * 5)

Multiply 8 * 4

32k + 9 * 5 = (36 + -4) * k + -1(2 * 5)

Multiply 9 * 5

32k + 45 = (36 + -4) * k + -1(2 * 5)

Reorder the terms:

45 + 32k = (36 + -4) * k + -1(2 * 5)

Combine like terms: 36 + -4 = 32

45 + 32k = (32) * k + -1(2 * 5)

Multiply 2 * 5

45 + 32k = 32k + -1(10)

Multiply -1 * 10

45 + 32k = 32k + -10

Reorder the terms:

45 + 32k = -10 + 32k

Add '-32k' to each side of the equation.

45 + 32k + -32k = -10 + 32k + -32k

Combine like terms: 32k + -32k = 0

45 + 0 = -10 + 32k + -32k

45 = -10 + 32k + -32k

Combine like terms: 32k + -32k = 0

45 = -10 + 0

45 = -10

Solving

45 = -10

User Kopiczko
by
6.2k points